A gestão do ensino em Suzano: o trabalho do coordenador educacional - Alamino, Patrícia da Silva Alecrim (2014)
The model of democratic and participatory management , based on the Federal Constitution (FC) 1988 and the Law of Guidelines and Bases of National Education (Law n.9394/1996) gives the school management team , responsibilities and autonomy in decision making processes and actions school. Our research analyzes the profile of the Educational Coordinator of Suzano after implantation of the Statute of the Job and Career Plan and its responsibilities within the school. The city of Suzano in 2010 implemented a number of proposed changes in the paradigms of educational management , in which is included the direct election for the position of Educational Coordinator. In developing this work firstly discuss an overview of the major Brazilian and global changes that have influenced the field of education in Brazil (World Bank/CF/LDBEN/Ten Year Plan/CONAE/municipalization). Subsequently, we analyze the model configuration and management of EMEIs EMEFs Educational System of the city of Suzano (since the historical aspects of the city, the municipalization process, the description of schools and the daily work of the school manager) . Closing the paper we present the first conclusions that can be drawn about the role of Coordinator in managing the municipal school in Suzano, according to the problems raised.